Clusters and spatial planning - Towards a research program - Jaap Vleugel (European Regional Science Association (ERSA), 2005)
Land is regarded as an important location factor by business firms. Firms change location due to internal and external factors and these changes should be accommodated by spatial reservations, subsequent land development and finally building of offices, plants or transhipment sheds. Business use of land competes with other uses of land, such as housing, leisure or nature. Spatial planning tries to balance these demands. Its success depends on finding criteria to justify a certain balance between economic and ecological interests or between different economic interests. Land-use should be included into a discussion about environmental sustainability. Spatial optimization would come at the agenda of firms and governments more often than is the case now. Yet, there is the issue of economic dynamics, which could be reduced if not all demands for new land are accommodated, at least according to business. This paper introduces a research program into the linkages between regional-economic-and spatial planning. It discusses the main ideas of this research program.
Keywords: 330